UMP and 3 foreign universities shared expertise in the manufacturing industry - Mohd Zairulnizam, Mohd Zawawi
Universiti Malaysia Pahang (UMP) and three other foreign universities - Iwate University of Japan, Hanbat University of Korea, Dang Liang University of China, pooled together their expertise in manufacturing industry involving the mold, die and casting technology and took part in the UURR Global Human Development Programme for Asian Manufacturing Industry 2013 in Iwate University of Japan on February 26, 2013.